Impact of Nature-based Learning on FLN Skills: Perspective and Approaches for ECCE Educators of Meghalaya - Momin, Nikme S.C.; Shullai, Ladakahi (THE PRIMARY TEACHER, 2025)
Nature-based learning offers a holistic and experiential approach to early education. It fosters a love for learning and provides a supportive context for developing foundational literacy and numeracy skills. This paper attempts to incorporate nature based learning into foundational education and study its impact on early learners’ foundational literacy and numeracy skills. The idea of nature-based learning is not new in India; it is deeply rooted in India’s traditional wisdom, knowledge systems and practices (Sharma & Kanaujia, 2020). However, owing to India’s colonial history and its urgent developmental challenges, a significant shift occurred in the values related to the environment, which has impacted the education system. NEP 2020 underscores the importance of adopting experiential learning in all stages of education (NEP Para 4.6). Nature-based learning is one of the best approaches to support the holistic development of children.